Applicative Constructions in Igbo (2020)
The structure of applicative constructions has been in debate due to diverse opinions regarding the categorial status and distribution of the applicative morpheme. Previous studies have focused on the morphemic structure with scant attention paid to the distribution and interaction of the applicative morpheme with other inflectional affixes. This study examines the syntactic distribution of the Igbo applicative morpheme with a view to determining its categorial status and base position in relation to other inflectional affixes such as tense, aspect and negation. Employing the split verb phrase hypothesis of minimalist program, the study reveals that Igbo applicative morpheme is a functor that projects maximally as an Applicative Phrase, showing up after the verb in the process of interacting with other inflectional elements. The study concludes that in deriving applicative constructions in Igbo, the verb enters the derivation with unvalued tense and applicative features which get valued as the verb moves from one head to another while the affixes get merged to the verb.